Introduction to Endoscopy for Urology Residents - Carley Davis; Margaret Mulligan (Association of American Medical Colleges, 2015)
Abstract Introduction Work hour constraints have decreased the amount of time available for resident teaching while the pressure to do so increases. This environment require focused, high-yield activities such as this workshop. This 4-hour Introduction to Endoscopy hands-on workshop was developed to familiarize incoming PGY2's with equipment assembly, disassembly, and trouble-shooting of endoscopy equipment. Methods During this training Urology residents in their first days of the cystoscopy suite rotated through several stations: rigid/flexible cystoscopy, rigid/flexible ureterosocopy, and standard/gyrus resectoscope. Through these stations learners became familiar with the basics of instrument assembly and handling, while the accompanying checklists confirm experience yet reaffirm proper use at each station. Results This workshop has been successfully conducted since 2012 with six residents. All residents have recommended it become a standard part of our Urology Curriculum. Additional workshop benefits included: decreasing overall resident anxiety regarding equipment, increasing efficiency, and assuring attending faculty that all residents had an established level of experience when in clinical settings. Discussion The greatest strength of this educational resource is its universality; it can be tailored to complement any curricula for all experience levels of learners. This course could also be applied to other surgical/medical specialties (i.e., ENT or GI) with similar equipment by simply swapping out the urology equipment with any instrument of choice and adapting the knowledge to be learned accordingly. Additional education in other endoscopic areas, or more advanced skills training, is not part of this introductory workshop structure. However, the workshop could be adapted to meet those needs.